Analysis of the Quality of the River Kualuh in the Review of the Physical-Chemical - Rosenta, Ika; Lihardo Hulu, Irwan; Harahap, Arman; Maini Hasibuan, Kiki; Nwazonobi, Patrricia; Mustika Piliang, Fenny (Publisher Cv. Inara, 2024)
The purpose of this study is to analyze the water quality of the river and the status of water quality of watersheds Kualuh Kabupaten Labuhanbatu. Sampling was done at 3 monitoring points along the flow of the river Kualuh Kabupaten Labuhanbatu. The determination of the sampling points in the field using the purposive sampling method, with the determination of the sampling points based on the differences in the characteristics found in the study area.Some of the parameters measured were temperature, conductivity, COD, BOD, and oil/ fat are then compared with the criteria of the Raw water Quality of the river class II according to PP R. I. No. 82 Year 2001.On Water Quality Management.Based on the results of the analysis of the obtained results that in the area of monitoring point 1, is the most polluted areas.This is because, in this area there is the activity of a diverse community.Household produces waste that comes from the activity of the bathroom, toilet, kitchen, washing clothes and washing of household appliances.